The mediating role organizational citizenship behavior between job attitudes and knowledge sharing behavior in private higher learning institution at Kota Kinabalu, Sabah (2015)
There are very few studies that examine impact of job attitude on knowledge sharing behavior. The purpose of this study is to investigate the effects of job satisfaction, job involvement and organizational citizenship behavior (OCB) on employees, knowledge sharing behavior. This study based on a survey of 326 individuals in private higher learning institutions in Kata Kinabalu, Sabah, Malaysia. Structural Equation Model (Partial Least Square approach, version 2.0) is used to test the hypothesis. The findings in this study show that, job satisfaction and OCB are independent and positively related to individuals1 knowledge sharing behavior. However, job involvement does not have direct relationship with knowledge sharing behavior. The current study confirmed that OCB is a significant mediator between job satisfaction, job involvement and knowledge sharing behavior. It is widely reported that knowledge is perceived as intangible assets to an organization especially the higher learning institution that act as the knowledge communication center, therefore, this study provides an in-depth understanding on the effect of job attitudes on the behavior to share knowledge. In practical, given the importance of knowledge sharing in today's knowledge-based economy, this study provides a better understanding for organization administrator to take proactive action to find out what are the factors that hindered the knowledge sharing behavior. The findings suggest that organizational administrators and managers should look into ways of improving the degree of job satisfaction, job involvement, and organizational citizenship behavior in order to facilitate knowledge sharing behavior. This study makes three distinct additions to the organizational behaviour and knowledge sharing literature. First, job attitudes appear to be significantly related to knowledge sharing behavior. Second, this study proposes that OCB not only has direct effect on knowledge sharing behavior at the same time it mediates individuals' job attitudes to promote knowledge sharing behaviors. Third, this study confirms the insignificant relationship between job involvement and knowledge sharing behavior.